Operation of a radio-controlled car using face images - Chomtip Pornpanomchai (2018)
The objective of this research is to operate a radio-controlled car (RC car) by using facial images. The research was conducted by taking a face image by a webcam and sending the image to a computer machine, and then the computer converted the face image into digital signal. After that, the digital signal was converted into a radio wave command. Finally, an RC car operated based on the radio wave commands. The experiment was conducted on the RC car with nine facial commands, which were: 1) Stop, 2) Forward, 3) Reverse, 4) Turn Left, 5) Turn Right, 6) Forward & Turn Left, 7) Reverse & Turn Left, 8) Forward & Turn Right, and 9) Reverse & Turn Right. The experimental precisions are 84.11%, 10.33% and 5.56% for match, mismatch and reject, respectively in the sufficiently lighted environment and 39.11%, 18.00% and 42.89% for match, mismatch and reject, respectively in an insufficiently lighted environment. © 2010 IEEE.